(untitled) (International Research Journal on Islamic Studies (IRJIS), 2023)
Many Muslim societies are facing such peacelessness, fear, horror, chaos, bloodshed, and killing today. One of the basic reasons for this is that there are no proper opportunities and aptly environment that nature has bestowed to human beings for saturating those subtle human emotions. However, we are floating with the changing trends of the world, such as the straws floating in the raging storm of the river, which do not have any existence and destination. While an important and extraordinary service of mysticism and Sufis on the other side for inculcating those subtle emotions in human beings which builds such a structure that the inhabitants of the society and promote the interfaith harmony after getting inspired are devoted for the reformation of the society. In fact, Hazrat Datta Ganj Bakhash (R.A) not only corrected the established futile system in the society with the teachings of reformation but also eradicated spread unlawful and invalid thinking about mysticism. Your ideology has made alive the correctness of beliefs and the soul of Taswuf in Islam from the origin which imputed the deep reforming aspects to promotion the peace & Interfaith harmony in the society and introduced new techniques to tackle the facing challenges of humanity in mysticism.